2016
DOI: 10.1097/sap.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Adipose-Derived Stem Cells From Abdomen and Breast

Abstract: Cells derived from both fat tissues possess different characteristics in terms of their growth kinetics and predisposition to the osteolineages and adipolineages. In particular, ASCs from the abdominal tissue appear to contribute to adipose tissue turnover, whereas ASCs from breast tissue, if used for cell-assisted fat grafting, may potentially be responsible for complications in fat grafting, such as oil cysts, calcifications, fat necrosis, and tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…The ASC sample phenotype was characterized as CD29+/CD44+/CD105+/CD45-. The results of surface markers were consistent with those of other studies [Guneta et al, 2016;Kim et al, 2017], and the cells isolated were confirmed to be ASCs. The results showed reduced expression of CD105 in WAT-ASCs compared to BAT-ASCs.…”
Section: Discussionsupporting
confidence: 91%
“…The ASC sample phenotype was characterized as CD29+/CD44+/CD105+/CD45-. The results of surface markers were consistent with those of other studies [Guneta et al, 2016;Kim et al, 2017], and the cells isolated were confirmed to be ASCs. The results showed reduced expression of CD105 in WAT-ASCs compared to BAT-ASCs.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas stem cells from the bone marrow are well characterized for their radiation sensitivity [ 16 ], studies on ADSCs are lacking or are carried out with mice as the host [ 17 ]. In addition, there are characteristic differences between adult stem cells isolated from adipose tissues of different origins, including growth kinetics [ 28 , 29 ]—a factor that may be responsible for tissue-specific radiation sensitivities [ 27 ]. From this reasoning, extensive analyses of underlying IR-induced mechanisms in ADSCs from different origins have to be performed in the future to engineer reliable cellular therapy options in radiation oncology.…”
Section: Discussionmentioning
confidence: 99%
“…18 Noteworthy is also the observation by Asterholm et al 19 that expression of inflammatory factors in adipocytes is required for adequate adipose tissue remodeling in response to energy intake. Noteworthy is also the observation by Guneta et al 20 who demonstrated marked differences between MSCs from breast fat and abdominal fat and it cannot be ruled out that ATMSCs-dependent graft survival depends on depot of origin. 21 …”
Section: Discussionmentioning
confidence: 99%